The impact of relationship quality and social support on social media users' selling intention. (8th October 2020) - Ho, Ree C.; Cheng, Robin
Social commerce is getting more popular with its sales volume increase rapidly, and drives more consumers to start conducting business in the social media. The main aim of this study was to investigate the role of social support and relationship quality in influencing the consumer selling behaviour. Sample size was 296 respondents collected via survey questionnaire and data was analysed with structured equation modelling. The results showed that user interaction in social media influenced the attitude needed to venture into online business. On the other hand, relationship quality and social support enhanced the consumers' perception on controlling the shopping process. In conclusion, the research findings provide insightful theoretical implications on the selling aspect of social commerce.